Social stress in rats promotes transcriptional mitochondrial changes of the adrenal tissue - Terese Elisabeth Zylla; Junbai Wang; Johannes Gjerstad (Endocrine and Metabolic Science)
Previous observations suggest that strong social stressors, that is, repeated social defeat, could initiate functional changes in the hypothalamic-pituitary-adrenal (HPA) axis in social mammals. Here, we examine whether exposure to such stress in rats causes persistent alterations in gene expression associated with hypo-and/or hyper-methylation in the adrenal tissue, i.e., the interface between the HPA axis and the circulating hormones. Our integrated analyses of RNA-sequencing (RNAseq) and whole genome bisulfite sequencing (WGBS), suggested that adrenal mitochondrial membrane transport necessary for corticosterone (CORT) synthesis, are affected by repeated social defeat. The increased CORT levels observed in blood in the stressed rats further suggested that corticosterone synthesis might be influenced by this form of social stress. The cellular mechanisms underlying these changes, i.e., the enriched gene ontology (GO)-terms and increased levels of circulating CORT, remain to be investigated.